Diabetes mellitus is associated with acquisition and increased mortality in HIV-uninfected patients with cryptococcosis: A population-based study. Issue 5 (May 2016) - Lin, Kuo-Hsi; Chen, Chih-Ming; Chen, Te-Li; Kuo, Shu-Chen; Kao, Chih-Chauan; Jeng, Ya-Chung; Ho, Mao-Wang
Summary: Objectives: To disclose the association between diabetes mellitus (DM) and cryptococcosis in HIV-uninfected patients. Methods: Case patients' diagnoses with cryptococcosis and cryptococcal meningitis were based on data from the Taiwan National Health Insurance Research Database from 2000 to 2010, and diagnoses were defined using the International Classification of Disease, Ninth Revision, Clinical Modification. A case–control study comprising inpatient and outpatient populations was conducted using 4 controls for each patient (4587 case patients and 18, 348 controls) matched for age, sex, monthly income, and urbanization level. Results: Human immunodeficiency virus (HIV)-uninfected patients with cryptococcosis were more likely to have diabetes than matched control patients (adjusted odds ratio [OR], 1.45; 95% confidence interval [95% CI], 1.36–1.64; p < 0.001). A diagnosis of DM was also associated with 1-year and overall mortality from cryptococcosis (hazard ratio [HR], 1.39; 95% CI, 1.17–1.65; p < 0.001, HR, 1.47; 95% CI, 1.29–1.67; p < 0.001; respectively) and cryptococcal meningitis ( p = 0.018). Conclusions: Diabetes was associated with the occurrence of cryptococcosis and cryptococcal meningitis in HIV-uninfected patients. DM was also associated with 1-year and overall mortality for these patients.